Advancement of animal reproductive biotechnology in South East Asia - Abdullah, Ramli; Khadijah, W.E.W.; Kanwal, K.D.S. (2001)
Reproductive biotechnology has contributed significantly towards increasing the livestock production in various developed countries. To maximize the productivity, reproductive potential of animals of economic importance in these countries has been fully exploited through the use of technologies such as artificial insemination, superovulation, embryo transfer, crossbreeding, oestrus synchronization, in vitro embryo production, cryopreservation of embryos and sperm, sexing of embryos, nuclear transfer, transgenesis and cloning. These technological developments have helped these countries immensely, to achieve self-sufficiency in animal products such as meat, milk and other by-products, and also in creating surpluses that bring revenues through exports. In addition, these technologies have also helped in conserving some of the endangered species of animals and in preserving the ecological balance. Unfortunately, the area of animal reproductive biotechnology has not been given due attention in South East Asian countries in developing livestock production and as a result the productivity of animals is low. This has led to a situation where most of these countries are not in a position to meet the local demands of animal food products and have to rely on imports. With the ever increasing population in these countries the impact of this deficit will be grave unless some serious measures are taken to increase animal productivity through the use of reproductive technologies. To investigate into the causes of low animal productivity in South East Asian countries this study was undertaken to review the scope and application of reproductive technologies. Unfortunately, reports on animal reproductive biotechnology are scarce and not readily available. Reports on some countries such as Brunei, Cambodia, Laos, Myanmar and Singapore could not be included in this study due to difficulty in obtaining the required information. Reproductive technologies such as artificial insemination, synchronization of oestrus, crossbreeding and embryo transfer, were introduced in these countries approximately 30 to 40 years ago for the improvement of indigenous livestock; however, the results have not been encouraging and most of these technologies are still at the infancy stages. Several constraints comprising of technical, physical, geographical, socioeconomic factors and policy related decision-making resulted in the unsatisfactory development of animal production. In order to uplift the status of reproductive biotechnology in South East Asian countries, it is imperative that these obstacles ought to be overcome first. Although in some of these countries, measures have already been taken by the respective governments and research organizations to develop good infrastructure and conduct research on reproductive technologies, such as in vitro production of embryos, micro manipulation of embryos and molecular studies. Still a lot has to be done before these countries can make real advancements on technology and economic fronts. This would only be possible by developing a large well-trained human resource and with mutual and international cooperation. In rapidly changing global scenario, South East Asian countries need to put lots of efforts to improve and increase their animal wealth and productivity through the use of latest reproductive biotechnology so as to reduce this gap with the developed nations. This would lead to a prosperous, economically independent, peaceful and stable future for the people of these countries.